Equinodermos (Echinodermata) del Golfo de California, México - Solís-Marín, Francisco A. (2005)
Echinoderms (Echinodermata) from the Gulf of California, Mexico. A systematic list of the echinoderms of the Gulf of California, based on museum specimens of the Colección Nacional de Equinodermos, Instituto de Ciencias del Mar y Limnología, Universidad Nacional Autónoma de México and the National Museum of Natural History, Smithsonian Institution, Washington, D.C. is presented. A total of 193 echinoderm species is recorded, distributed in 108 genera, 51 families and 19 orders. 12 new records for the Gulf of California are presented: Asteroidea (four), Ophiuroidea (three) and Holothuroidea (five). Rev. Biol. Trop. 53(Suppl. 3): 123-137. Epub 2006 Jan 30.